O uso de mídias interativas na compreensão de conceitos da lógica computacional - Ramos, Reinaldo Augusto de Oliveira (2011)
This paper introduces the possibilities of using informatized interactive systems in effectively teaching computer logics and the development of logic thinking and its implications. It is about experiment and analysis accomplished in educational institutions in the city of São Paulo, having the directive to observate the given hypothesis: games and their developing tools can work as methodological resources to the teaching-learning process in the development of the conception of logic programming as used with intentionality. To progress in educating students on logic programming and in mathematical abstraction, it is proposed the development of electronic games through singular tools level editors, simplified scripts and visual programming environments. These help develop propositions, digital productions, animations, sounds and other interactive resources with the objective of working and problematizing in practical environments and of arranging facts and simulated experiments to understand logics. Using development indicators in the evolution processes of students, individual cases were studied, in which it was observed the way the teaching-learning process works, from propositions faced during the game production. Through the discussion, it was analysed the importance of different kinds of tools used to teach and learn the programming logic contents. Therefore, this study is based on theoretical references provided by Jean Piaget s constructivism Lev Semenovitch Vygostky s social-historical approach and Seymour Papert s and José Armando Valente s constructionism. We seek in these methodologies, in special Vygotsky s Proximal Development Zone theory, the key to the pedagogic base of the methodology here proposed. Coming to the conclusion, this present work confirms the hypothesis that games and their development tools can be na adequate instrument for studentes to understand programming logics. It also has a bibliographic revision on interactive media, culture and also education and information science